Penggunaan Data Unmanned Aerial Vehicle (UAV) untuk Pembuatan Data Geometrik dalam Pemodelan Banjir Sungai (The Use of UAV Data for Creating Geometric Data in Riverflood Modeling) - Wahyu Wisnu Wijaya; Slamet Suprayogi; Andung Bayu Sekaranom; Hendy Fatchurohman (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2024)
In the last 10 years, flood modeling has been used to describe the geospatial phenomenon of flooding in an area. Flood modeling analysis uses river geometric data as one of the inputs. River geometric data is obtained through image analysis and Digital Elevation Model data derivatives. Accuracy in creating river geometric data influences the modeling results. The limitations of both high cost and the influence of weather conditions from satellite data sources made photogrammetry techniques using UAV drones increasingly popular. This research aims to: 1). Create orthophotos and DEM with high accuracy of the location of flood areas, 2). Creating river geometric data for flood modeling, and 3). Modeling river floods with HEC-RAS software. This research uses Agisoft Photoscan software to process the resulting aerial photos. The results of testing the accuracy of DEM and orthophoto data obtained a vertical accuracy/ Linear Error (LE90) value of 1.029 m and a horizontal accuracy/ Circular Error (CE90) value of 0.214 m. The resulting orthophoto and DEM have high accuracy so they can be used as input in the modeling process. The result of high-resolution model will be able to provide a quick and accurate picture of geospatial phenomena. The flood model produced using HEC-RAS software shows that floods inundate an area of 120.14 ha in a return period of 2 years and 203.21 ha in a return period of 50 years.